A comparison of multidimensional qualities discriminant of selection in elite adolescent Australian basketball athletes - Joseph, J.; McIntyre, F.; Joyce, C.; Scanlan, A.; Cripps, A. (PLOS ONE, 2021)
Purpose: The aims of this study were to (1) quantify the multidimensional attributes of male and female basketball athletes under 16 years of age (U16) and under 18 years of age (U18), and (2) identify attributes that distinguish selection into a talent pathway according to sex and age group. Methods: 67 male and 71 female athletes competing in U16 and U18 selection trials for a state based Australian basketball talent pathway completed a multidimensional testing battery. The test battery consisted of anthropometric, physical (20- linear sprint, countermovement jump height, Yo-Yo Intermittent Recovery Test Level 2), technical (Basketball Jump Shooting Accuracy Test), tactical (video decision making), and psychological (Sports Orientation Questionnaire, Psychological Performance Inventory-Alternative) assessments. Mean differences and independent t-tests were used to assess comparative differences between selected and non-selected athletes within each age and sex cohort. Stepwise discriminant analyses were used to identify attributes that were the strongest discriminators of selection in each group (male U16, male U18, female U16, and female U18). Results: The discrimminant models showed for male U16 athletes smaller height (ES = -0.18) and greater shooting accuracy (ES = 0.52) was most discriminant of selection. Results were largely homogenous for male U18 athletes with lower visualisation score (ES = -0.62) most discriminant of selection. In female cohorts, faster 20-m sprint time (ES = -0.66) and taller height (ES = 0.58) was most discriminant of selection in U16 athletes while greater shooting accuracy (ES = 0.67), countermovement jump height (ES = 1.04), and height (ES = 0.65) was most discriminant of selection in U18 athletes. Conclusions: These results emphasise the differing selection priorities within adolescent basketball cohorts according to sex and age group. The testing of anthropometric, physical and technical attributes may hold particular utility in adolescent female basketball given their identified importance to selection across U16 and U18 cohorts.